(untitled) (Journal of Applied Membrane Science & Technology, 2023)
Ineffective dyeing procedures frequently lead to the release of approximately 10–50% of the dye applied, which does not adhere to the fabric and is consequently discharged into the environment along with the effluent. This situation is undesirable both for potential recycling within the textile manufacturing process and because of its adverse environmental pollution effects. This study thoroughly examines nanofiltration (NF) membrane characteristics and their performance in textile wastewater treatment. Pristine NF membrane surfaces were revealing a web-like structure with well-defined pores predominantly in the membrane active region. This assessment confirms the membrane initial cleanliness, free from any external contaminants, which is vital for effective membrane-based filtration. Additionally, the study investigates how different feed flow rates affect water flux during NF membrane filtration. The results demonstrate a clear relationship, where the increasing flow rates boost water flux. This can be attributed to heightened cross-flow velocity and shear force on the membrane surface due to the increased water flux, minimizing external concentration polarization and reducing membrane fouling. The impact of feed flow rate on membrane separation efficiency is also examined, showing consistent efficiency at feed flow rates between 2 LPM and 5 LPM (approximately 80.8% to 82.22%). However, efficiency drops as the feed flow rate increases from 5 LPM to 6 LPM, likely due to increased pressure drop across the membrane, affecting separation efficiency.